The Economic Impact of Service Quality on Company Image, Customer Trust, and Loyalty: A Study on Savings Customers at Bank Syariah Indonesia (BSI) - Moenardy, Khalid Kasim; Kasim, Abas; Messakh, Anthon B.; Astuti, Indri; Bessie, Juita L.D. (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to investigate the influence of service quality variables on the company's image, customer trust and customer loyalty, as well as the influence of company image variables on customer trust and customer loyalty, and the influence of trust on customer loyalty. To achieve these objectives, accidental sampling selected 70 customers of Bank BSI as respondents. Selection of sample customers using the criteria: (a) have a minimum savings amount of Rp 5 million, and (b) have been saving at Bank BSI for at least one year when this research was conducted. To achieve the first objective, descriptive analysis was used and GSCA (Generalized Structured Component Analysis) was used to achieve objectives two to six. The results of the analysis show that customers perceive service quality and customer trust, including in the very high / very good category, while company image and customer loyalty are in the high / good category. While the results of GSCA analysis show: (a) service quality has a significant and positive effect on corporate image; (b) service quality has a significant and positive effect on customer trust; (c) service quality has a significant and positive effect on customer loyalty; (d) corporate image has a significant and positive effect on customer trust; (e) corporate image has a significant and positive effect on customer loyalty; and (f) customer trust has a significant and positive effect on customer loyalty. Further research (with the same object: BSI customers) by adding independent variables and expanding the research area, especially in areas where the majority of the population is non-Muslim, such as in the Maluku, Papua and North Sulawesi regions, needs to be carried out. The management of BSI Kupang Branch is advised to strategically strive to improve service quality, corporate image and customer trust on an ongoing basis, and at the same time, continue to improve customer loyalty, so that customers remain customers of BSI Kupang Branch.